Between Efficiency and Authenticity: Generation Z Students Negotiating Artificial Intelligence in Everyday Social Media Practices - Dwi Maharani; Septiawan Santana Kurnia; Neni Yulianita; Anne Ratnasari; Oji Kurniadi (Jogjakarta Communication Conference (JCC), 2026)
The integration of Artificial Intelligence (AI) into digital platforms has transformed the way social media content is produced and managed. For Generation Z, particularly university students, use of AI has become part of everyday communication practices that not only offer efficiency but also raise questions about authenticity and ethics in self-representation. This study aims to analyze how Generation Z students negotiate the use of AI in social media practices, particularly in the context of self-presentation. This research employs an interpretive qualitative approach, with data collected through in-depth interviews with seven communication studies students who actively use social media platforms such as TikTok and Instagram. Data analysis was conducted using the interactive model of Miles and Huberman. Results show that students actively use technology, including AI tools such as ChatGPT and editing applications like CapCut and Canva, in the content production process. However, AI is not used comprehensively; rather, it is selective, mainly to assist with idea development and caption writing. Students still maintain control over personal aspects to preserve the authenticity of their identities. The main findings indicate a negotiation between efficiency and authenticity in self-presentation practices. Although AI provides convenience in content production, students set boundaries when using technology to maintain authenticity and credibility with their audience. Additionally, these practices are influenced by ethical considerations, including the values of honesty (sidq), intention (niyyah), and caution against excessive self-display (riya’) on social media. This study contributes to the field of digital communication by demonstrating that the use of AI in social media practices is not deterministic but rather a process of negotiation involving technological, social, and ethical dimensions. These findings also enrich the literature by offering a contextual perspective on Generation Z in Indonesia, helping to understand the dynamics of self-presentation in the era of Artificial Intelligence.